2011
DOI: 10.1128/jb.05811-11
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and Phylogenetic Analyses of the Mycobacterial mbt Gene Cluster

Abstract: The mycobactin siderophore system is present in many Mycobacterium species, including M. tuberculosis and other clinically relevant mycobacteria. This siderophore system is believed to be utilized by both pathogenic and nonpathogenic mycobacteria for iron acquisition in both in vivo and ex vivo iron-limiting environments, respectively. Several M. tuberculosis genes located in a so-called mbt gene cluster have been predicted to be required for the biosynthesis of the core scaffold of mycobactin based on sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 51 publications
1
60
0
Order By: Relevance
“…Subsequent genetic studies confirmed that this gene cluster was associated with MBT production in M. tuberculosis (4). Analyses of the homologous clusters from Mycobacterium smegmatis (3) and Nocardia farcinica (15) confirmed that they were involved in the biosynthesis of MBT and the analog nocabactin NA, respectively, providing additional support for the idea that these gene clusters are involved the production of MBT and MBT-like siderophores.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Subsequent genetic studies confirmed that this gene cluster was associated with MBT production in M. tuberculosis (4). Analyses of the homologous clusters from Mycobacterium smegmatis (3) and Nocardia farcinica (15) confirmed that they were involved in the biosynthesis of MBT and the analog nocabactin NA, respectively, providing additional support for the idea that these gene clusters are involved the production of MBT and MBT-like siderophores.…”
mentioning
confidence: 50%
“…Filtration and concentration yielded a colorless clear oil. The crude material was purified on silica with 33:1¡30:1 DCM-methanol containing 0.1% NH 3 Synthesis of N 6 -hydroxy-L-Lys (4). 3 (38 mg, 0.11 mmol) was dissolved in DCM (1 ml) in a vial under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Our results also show that inactivation of siderophore export and recycling delivers a onetwo punch to Mtb by reducing its capacity to take up iron and by siderophore-mediated self-poisoning. For these reasons, targeting siderophore secretion appears to be advantageous compared with biosynthesis (22,45) because inhibition of siderophore biosynthesis is easily overcome by Mtb using heme, in contrast to siderophore secretion (14). However, when and how Mtb gains access to different iron sources during infection is unclear, as are many components of its iron acquisition mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxamic acid groups (N-OH) of the ε-Nhydroxylysines, the phenolate oxygen atom, and the nitrogen atom of the oxazoline moiety (circled in Fig. 1) chelate Fe 3ϩ very effectively, explaining the high affinity of the molecule (ϳ10 30 ) for the oxidized form of the metal ion (8), with poor binding seen with Fe 2ϩ . Figure 1 shows the substitutions at R1 to R5 contributing to the variations among the mycobactins produced by different mycobacterial species.…”
Section: ϫ7mentioning
confidence: 99%